Neuroplasticity and its Relationship to Thinking Patterns among Sample of Educational Counselors in Jordan - Jolban, Moawiah Falah Abo; ALrosan, Duha ahmad abdelrahman; Alaboud, Khadija Abdallah Abdalhafez; Rababa, Elham Mahmoud; Al-Momani, Mohammad Omar (Journal of Ecohumanism, 2024)
The study aimed to uncover neuroplasticity and its relationship to thinking patterns among a sample of educational counselors in Jordan. The study aimed to identify differences according to the variables of gender and social status. The study sample consisted of (216) male and female counselors (114 male and 102 female). They were randomly selected, and to achieve the objectives of the study, two scales were developed: The Neuroplasticity Scale and the Thinking Patterns Scale, and the reliability and stability of the two scales were verified and then applied to the study sample. The results showed that the level of neuroplasticity and the level of thinking patterns of counselors were high, and the results indicated that there were no statistically significant differences in the level of neuroplasticity due to the variables of gender and social status, and the results also indicated that there was no statistically significant correlation in the thinking patterns of counselors